A comparative study of Primary Education System in India and Bhutan (Focus on Indian Rural Primary Schools) (Proceedings of the International Conference on Future of Education, 2019)
Education is the most vital vehicle making our journey in life meaningful, valuable and rewarding and with it, one could turn dreams into realities and become successful. Unfortunately, in many developing countries’ low literacy rate and low per capita income lead them to below poverty line. In India, factors like gender, caste, school factors, social factors and rural- urban inequalities hamper in achieving the minimal development goals. Besides, a high dropout rates from Indian school system is a great concern for a nation marked by one of the largest populated countries in the world .The paper seeks to understand the reasons for poor retention of students and teachers and their related issues that impacted educational access in rural primary schools in India. Moreover, Bhutan too suffer from similar issues such as poor infrastructures , declining education quality, social and economic disparities despite many policies, plans and programs in place. The investigation through education access, structure, educational quality and rural primary school curriculum of India is expected to bring in understanding about necessary remediation as India and Bhutan constantly face correlatives issues at the rural front.
Keywords: Rural primary school system, educational access, education challenges, education for all.